KURIKULUM SISTEM MAYOR-MINOR SEBAGAI REFERENSI PENGEMBANGAN KURIKULUM2002 PROGRAM STUDI PJKR FAKULTASILMU KEOLAHRAGAAN UNIVERSITAS NEGERI YOGYAKARTA - - Komarudin (Jurnal Pendidikan Jasmani Indonesia, 2006)
Abstract: This article aim to give description on 2002 curriculum development of PhysicalEducation Programme Study, Health and Recreation (PJKR Programme study), FIK UNYthrough analyzing major-minor curriculum system, a curriculum which is effective on thetime of FPOK or Sport and Health Education Faculty of IKIP Yogyakarta, founder of FIKUNY. This curriculum was known as 1992 curriculum or flexible curriculum even it wasmade before Competence Based Curriculum. This curriculum, however, has give descriptionon how graduate competence has been reconstruct for increasing scholars competencyand nation competency in the global era.Keyword: Curriculum, major-minor system.